Survey Kepuasan Wajib Pajak dan Kajian Peningkatan Pelayanan Pajak Daerah Kabupaten Tanjung Jabung Barat - Pantun Pantun; Muhammad Syukri; Hana Tamara Putri (Ekonomis: Journal of Economics and Business, 2022)
This study aims to determine and analyze the description of the characteristics of taxpayers, taxpayer satisfaction levels, performance levels and the importance of service quality attributes, analyze direct and indirect effects and efforts to improve tax services in West Tanjung Jabung Jabung Regency. The research method used in this study is explantory. survey, while the approach used is quantitative. In analyzing the data used descriptive statistical techniques that function to classify data, work on, conclude, describe and present the processed results. Of the five dimensions of service characteristics in evaluating service quality, namely Tangibles, which includes physical facilities, equipment, employees and communication facilities are in the very satisfied category, reliability, namely the ability to provide services immediately, accurately and satisfactory and in accordance with what has been promised are in the satisfied category, Responsiveness, namely the desire of the staff to help customers and provide services responsively are in the satisfied category, Tangible Direct and Indirect Effects  Towards Satisfaction of Regional Taxpayers in West Tanjung Jabung Regency of 0.118; Direct and Indirect Effects of Reliability on Satisfaction of Regional Taxpayers of Tanjung Jabung Barat Regency of 0.081; Direct and Indirect Effects of Responsiveness Towards Satisfaction of Local Taxpayers K Tanjung Jabung Barat Regency is 0.134; Direct and Indirect Effects of Assurance on Regional Taxpayer Satisfaction in West Tanjung Jabung Regency is 0.134; Direct and Indirect Effects of Empathy on Compulsory Satisfaction Regional Tax of Tanjung Jabung Barat Regency is 0.346;, the results of the Independent Sample T-Test, obtained a T-Test Value of 0.000 where 0.000 <0.05 means that there is a significant difference between efforts to improve tax services that have been carried out by the BPPRD office. with Taxpayer Expectations.